PENERAPAN MODEL PEMBELAJARAN BERBASIS PORTOFOLIO DALAM MENINGKATKAN KEAKTIFAN BELAJAR BAHASA ARAB PADA SISWI SMAI SUNAN GUNUNG JATI DI ASRAMA PUTRI SUNAN PANDANARAN NGUNUT - Mardiyah, Hanik Shofa; Rois, Fatqu; Riyanto, Riyanto (STAI KH. Muhammad Ali Shodiq, 2023)
Portfolio is a learning model that can be applied by teachers so that students have the ability to express their opinions both individually and in groups. In a portfolio, a student can measure the extent of understanding he has gained from a learning process. This research aims to describe the application of the portfolio-based learning model to SMAI Sunan Gunung Jati female students in the Sunan Pandanaran Ngunut female dormitory, especially in increasing student activity in learning Arabic. The method used in this research is descriptive qualitative with field research type. The results of the research show that the portfolio-based learning model used by Arabic teachers at SMAI Sunan Gunung Jati can identify the extent of students' understanding in the learning process and also increase students' interest and activeness in learning Arabic. The steps of the portfolio-based learning model are; introduction of topics by the teacher, selection of problems by students, search and collection of information, making portfolios in groups, presentations, and conclusions. Keywords: Student Activeness, Portfolio Learning Model